EP862 Double rare association of malignant ovarian tumors: endocrine and lymphoma ovarian tumors a bout one case. (1st November 2019) - Hadjarab, F; Chekman, CE; Taibi, A; Bouzid, K
Abstract : Introduction/Background: The ovarian tumours are rare, often latent andof fortuitous discovery. The ovarian endocrinetumours, remain in spite of their scarcitypotentially malignant. The ovarian lymphomas not hodgkiniens areexcrement rare, accounting for 1.5% fromovarian cancers and 0.5% of the lymphomasnot hodgkiniens. Methodology: We report a rare case of associating anovarian endocrine tumour and an ovarianlymphoma controlatéral at a 61 years oldwoman, revealed approximately a year ago byabdominal pains of the right side. Abdominalechography, it to scan thoraco-abdomino-pelvic and the MRI abdominal assembled ametastatic liver multi nodular, a left ovarianmass and adenopathies retro péritonéales. 4months later, the patient is operated (Colpo hysterectomy, bilateral annexectomy, metastasectomy of segment IV of the liver). Results: The examination anatomopathologicconcluded with a diffuse lymphoma with largecells from phenotype B (CD20 +) of uterine seat latéro hepatic left andthe localizations and ovarian right-hand side ofa tumour neuro endocrine gooddifferentiated from rank 2. The assessment of extension (colonoscopy, angio to scan thoraco abdomino pelvic) in particular showed ametastatic liver, a ascite of low abundance, adenopathies retro péritonéales, ganglia interbronchial and hilaires and a pericardialoutpouring. On the endocrinal level, there are in addition no obviously signs of NEM1 or ovarian hypersecretion. The patient currently treatedby poly chemotherapy (RCHOP), shows apartial answer estimated according to the imagery at 50%. Conclusion: The association of these 2 ovarian tumoral forms is exceptional and must be to discuss in RCP (DIALOGUE MULTIDISCIPLINARY OF THEDOCTORS FOR DISCUSSION OF THE FILES OF THE PATIENTS) for an optimal assumption of responsibility the two diseases. Disclosure: No any confilct of interest.